Rezim Persahabatan ASEAN dalam Tata Kelola Lintas Perbatasan Darat Indonesia-Malaysia Berbasis Connectivity - Saptopo B Ilkodar (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2012)
This article elaborates compatibility of ASEAN’s value with that of the idea of Indonesia-Malaysia borderland governance based on connectivity and common prosperity. It compares the basic value of ASEAN’s regime on amity on the one hand, with that of the borderland governance on the other. The result shows that the two concept are compatible on the surface but contradict to each other in the deeper layer. The idea of Indonesia-Malaysia borderland governance together with ASEAN Connectivity could potentially replace the nature of intra ASEAN relationship of solidarity to business partner.